ANTITUSSIVE ACTIVITY ASSAYOF SAGE (LANTANA CAMARA L.)LEAVES BASED ON THE BREATHING PATTERN OF MALE GUINEA PIGS USING ADOBE AUDITION 1.5 PROGRAM - Yuliastri, Wa Ode; Soemardji, Andreanus; Ifaya, Mus (International Journal of Current Pharmaceutical Research, 2017)
Objective: The present study was aimed to assay antitussive activity of Sage (Lantana camara L.)leaves Methods: Antitussive Assay was conducted based on The Breathing Pattern of Male Guinea Pigs Using Adobe Audition 1.5 Program. Results: Comparison of the frequency of breathing patterns guinea pig groups sage (Lantana camara L.)Â leaves water fraction at a dose of 4.58 mg/kg bw dose of 9.17 mg/kg bw and doses of 18.35 mg/kg bw statistically significantly different results (p<0.05), as well as the ratio of intensity of the breathing pattern of the guinea pig. As for the water extract, significant differences in the frequency comparison guinea pig respiratory pattern is only shown at a dose of 18.35 mg/kg bw on the other side for its intensity did not show significant differences (p<0.05). Conclusion: Ethanol extract of sage leaves in the form of three fractionation (ethyl acetate, n-hexane, and water) can improve the breathing pattern guinea pig cough, especially at a dose of 18.35 mg/kg bw. Â